2020
DOI: 10.1371/journal.pone.0240885
|View full text |Cite
|
Sign up to set email alerts
|

Whole egg consumption increases gene expression within the glutathione pathway in the liver of Zucker Diabetic Fatty rats

Abstract: Nutrigenomic evidence supports the idea that Type 2 Diabetes Mellitus (T2DM) arises due to the interactions between the transcriptome, individual genetic profiles, lifestyle, and diet. Since eggs are a nutrient dense food containing bioactive ingredients that modify gene expression, our goal was to examine the role of whole egg consumption on the transcriptome during T2DM. We analyzed whether whole egg consumption in Zucker Diabetic Fatty (ZDF) rats alters microRNA and mRNA expression across the adipose, liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The enriched pathways identified in the IAA group were primarily involved in metabolism, including retinol metabolism, xenobiotic biodegradation and metabolism, and the metabolism of terpenoids and polyketides. The increased abundance of retinol metabolism was also found in lean control rats compared with diabetic fatty rats (105). Terpenoids and polyketides are bioactive substances, and the metabolism of terpenoids and polyketides was significantly increased after weight loss in obese mice (106).…”
Section: Discussionmentioning
confidence: 83%
“…The enriched pathways identified in the IAA group were primarily involved in metabolism, including retinol metabolism, xenobiotic biodegradation and metabolism, and the metabolism of terpenoids and polyketides. The increased abundance of retinol metabolism was also found in lean control rats compared with diabetic fatty rats (105). Terpenoids and polyketides are bioactive substances, and the metabolism of terpenoids and polyketides was significantly increased after weight loss in obese mice (106).…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, the literature indicates that dysregulated GST production has been implicated in conditions of obesity and T2D ( 41 ). It was previously reported that glutathione metabolism is regulated by egg yolk peptide consumption in a porcine model of oxidative stress ( 42 ), while in Zucker Diabetic Fatty rats WE consumption led to an upregulation in 14 GST-related enzymes across numerous tissues ( 43 ). In a meta-analysis of clinical studies with long-term egg consumption, there were no observed effects of WE consumption on blood inflammatory markers ( 44 ).…”
Section: Discussionmentioning
confidence: 99%